Amphiphilic polymer coated nanodiamonds: a promising platform to deliver azonafide. Issue 15 (14th March 2019) - Lai, H.; Lu, M.; Chen, F.; Lalevée, J.; Stenzel, M. H.; Xiao, P.
Abstract : An amphiphilic polymer is grafted on nanodiamonds to improve the colloidal stability and to deliver an anticancer drug azonafide. Abstract : Nanodiamonds (NDs) are attracting increasing attention as drug delivery systems due to their outstanding mechanical and optical properties as well as excellent biocompatibility. However, the strong tendency to agglomerate limits their use in biological medium, especially when adsorbed hydrophobic compounds. Polymer coating is a convenient approach to enhance the colloidal stability and place therapeutic drugs. Here, we report an epoxy containing amphiphilic block copolymer poly( n -butyl methacrylate- co -polyglycidol methacrylate- block -poly(oligoethylene glycol methyl ether methacrylate)) (PBA- co -PGA- b -POEGMEMA) for coating NDs. The resultant polymer coating significantly reduced the particle size and enhanced the colloidal stability. The inner hydrophobic block was exploited to encapsulate hydrophobic anticancer drug-azonafide. The cytotoxicity of the azonafide-loaded NDs was evaluated by 2D and 3D models. Although azonafide encapsulation displayed higher IC50 than free azonafide in the 2D breast tumour cell culture model, the former showed accelerated cytotoxicity than free azonafide in the 3D breast multicellular tumour spheroids. The results indicate the amphiphilic polymer coated NDs could be a promising carrier for azonafide due to the facile synthesis protocol, the potential to reduce side effects and the enhanced toxicity.